Juvenile diversion: keeping children out of prison - Lewis, Sharon (Rhodes University, Faculty of Law, Law, 1997)
This thesis covers the topic of juvenile diversion with respect to keeping juveniles from progressing further into the justice system as well as keeping them out of prison. It deals with a number of areas. The first is diversion before an offence has been committed - prevention. Here a number of recommendations are made with respect to education of the child and the community in order to make prevention a priority when new diversion programmes are considered and introduced. The second area is that of diversion after the offence has taken place. This deals with diversion by the police at the moment of apprehension and recommends the introduction of cautions as a diversionary measure. The third aspect that is considered is diversion after the juvenile has been arrested and/or charged. The establishment of Reception and Assessment Centres and the setting up of Family Group Conferences are especially highlighted. The detention of the child until his/her trial is also investigated and it is concluded that this is an unnecessary measure except in extreme circumstances. The progression of the child's case to court is the fifth area considered. Here, recommendations are made as to the necessity for the proper training of court personnel and the need for the introduction of court imposed diversionary programmes before sentencing. With respect to diversion after the child has been found guilty, a number of suggestions are made as to the introduction of new sentencing options and new or improved institutions. Finally, recent reforms are discussed. The conclusion reached is that juveniles should not be imprisoned except in the most extreme cases, and that diversion programmes should be instituted as soon as possible as the basis of SouthAfrica's juvenile justice system. It is deemed essential that diversion begins with prevention and continues until sentencing is completed, and that all children are diverted unless this is not possible.
Keywords: Juvenile delinquents -- South Africa; Juvenile justice, Administration of -- South Africa